Delayed-onset disseminated BCG disease causing a multi-system illness with fatal mycotic aortic aneurysm. (January 2023) - Tregidgo, Laura; Hammond, Robbie; Bramley, Alexandra; Davis, Meryl; Morshed, Ahmed; Patel, Anant; Pradhan, Anuja; D'Cruz, Rebecca F.; Lipman, Marc
Highlights: Disseminated BCG can occur months to years after intravesical BCG infusion and should be considered in such patients presenting with pyrexia of unknown origin. Obtaining tissue samples for microbiological diagnosis (including for mycobacteria) through PCR and culture is important. Mycotic aneurysms are a rare but serious complication of disseminated BCG with a high mortality. Finding effective treatment for BCGosis with mycotic aneurysm is difficult, given intrinsic resistance to pyrazinamide, and concerns over use of fluoroquinolones. Further published information on the average duration from BCG intra-vesical infusion to presentation of serious complications is needed. Abstract: Case: We report a case of disseminated BCG infection, diagnosed two years after BCG infusion for bladder cancer. Our patient, a 74-year-old male, was referred with an 18-month history of fevers, weight loss and intermittent confusion. Prior to referral, the patient had multiple hospital admissions for evaluation of fever of unknown origin, confusion, and fatigue. He was treated for several acute infections, whilst extensive investigations did not identify a focal cause of the persistent fever. During this period two aneurysms, iliac and aortic, were found and stented. Both were presumed mycotic, but no positive microbiology arose from either. He presented again with fever and confusion and was found to have a left sided pleural effusion, which was drained, and broad-spectrum antibiotics started, but his fever and inflammatory markers did not settle. Mycobacterium tuberculosis PCR on a pleural fluid sample returned a positive result, and later cultures from the same fluid grew Mycobacterium species which whole genome sequencing identified as Mycobacterium Bacillus Calmette-Guérin (BCG). Despite a number of adverse events with anti-BCG medications, the patient was established on four medications (rifampicin/isoniazid/ethambutol/levofloxacin) with symptomatic improvement. He re-presented four months later with abdominal pain and was found to have an inoperable leaking thoracic aortic sac from deterioration of his mycotic aneurysm. Following discussion with the patient and his family he was managed palliatively and died two days later. Discussion: The learning points from this case are to consider disseminated BCG in patients presenting with pyrexia of unknown origin following reported intravesical BCG treatment for bladder malignancy in the years prior to presentation. Mycotic aneurysms are a rare but serious complication of disseminated BCG with a high mortality.